2010
DOI: 10.1099/vir.0.020404-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogeography of begomoviruses infecting legumes in Pakistan

Abstract: Grain legumes are an important source of dietary protein across southern Asia, but they suffer extensive losses due to several viruses that are members of the genus Begomovirus (family Geminiviridae), which are collectively known as legume yellow mosaic viruses (LYMVs). Despite their economic importance, little attention has been paid to LYMVs in Pakistan and only partial sequences of virus isolates originating from this country are available in the databases. Here, a survey of LYMVs occurring across Pakistan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 28 publications
5
69
0
1
Order By: Relevance
“…The hypothesis of genetic isolation of legume yellow mosaic viruses (LYMVs) has been put forward hence genetic recombination or genomic components exchanges are rare (Qazi et al, 2007;Ilyas et al, 2010). Supporting the hypothesis, all the recombination events detected in this study are between Old World begomoviruses (Fig 3a and Fig 3b and Supplementary table 3 and Supplementary table 4).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The hypothesis of genetic isolation of legume yellow mosaic viruses (LYMVs) has been put forward hence genetic recombination or genomic components exchanges are rare (Qazi et al, 2007;Ilyas et al, 2010). Supporting the hypothesis, all the recombination events detected in this study are between Old World begomoviruses (Fig 3a and Fig 3b and Supplementary table 3 and Supplementary table 4).…”
Section: Discussionsupporting
confidence: 70%
“…The situation warrants serious management techniques to tackle YMD disease of soybean in central India. In this context, it is pertinent to mention begomoviruses and their beta satellites which were not considered as pathogens of grain legumes were found to involve in genetic recombination while analyzing genetic diversity and phylogeography in Pakistan (Ilyas et al, 2010). Likewise, a novel legumovirus Soybean chlorotic blotch virus (SbCBV) found to be infecting soybean in Nigeria was characterized with genomic components identical to the virus infecting wild species Centrosema pubescens (Alabi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have demonstrated that weeds would serve as a reservoir or alternative hosts for begomoviruses survival and spread [4,11]. The possible contribution of weeds in the evolution of cropinfecting begomoviruses via genetic recombination [12] strongly underscores the importance of characterization of begomoviruses infecting weeds.…”
Section: Introductionmentioning
confidence: 98%
“…Begomoviruses belonging to OW are further differentiated into viruses from Africa, India, Asia, and Japan. Two groups of viruses, those infecting legumes in Africa, India, and South East Asia (Legumoviruses) [4] and viruses that infect sweet potato are distinct from all other OW begomoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Although weeds do not appear to be significant reservoirs of crop-infecting viruses, they are found to be natural reservoirs for some of the agriculturally significant begomoviruses [7][8][9][10]. Considering the importance of weeds harboring many begomoviruses [11,12], during the year 2010, a study was undertaken for the identification and characterization of the begomovirus species which are associated with native weeds.…”
mentioning
confidence: 99%